Trends in palliative care utilization among older adult decedents with and without cancer in Taiwan: a population-based comparative studyResearch in context - Yu-Tai Lo; Tzu-Jung Chuang; Yu-Tung Huang; Yi-Lin Wu; Yi-Ching Yang; Chung-Yi Li (The Lancet Regional Health. Western Pacific)
Summary: Background: The leading causes of death among the older adults have shifted from cancer to non-cancer conditions such as ischemia heart diseases, stroke, and dementia, affecting end-of-life care needs. This study examined the difference in the proportion of palliative care utilization in relation to specific causes of death and compared the trends in palliative care utilization between older adult decedents with and without cancer in Taiwan from 2010 to 2020. Methods: The study utilized data from the Health and Welfare Data Science Center in Taiwan, covering demographic and healthcare variables for 588,010 decedents aged 65+ years who died between 2010 and 2020. We used Poisson regression to investigate the temporal trends in palliative care utilization during the last six months of life. Multivariable logistic regression models were constructed to analyze cancer, and non-cancer causes of death associated with palliative care utilization. Findings: The proportion of palliative utilization in cancer deaths started at 21.7% in 2010 and increased to 63.2% by 2020 with the beta coefficient of 0.09 (95% CI: 0.09–0.09). The proportion of palliative utilization in non-cancer deaths started at 0.8% in 2010 and increased to 23.5% by 2020, with the beta coefficient of 0.26 (95% CI: 0.26–0.26). Compared to deceased cancer patients, deceased non-cancer individuals were less likely to have received palliative care (OR = 0.12, 95% CI: 0.12–0.13). Interpretation: Efforts to ensure equitable access to palliative care for non-cancer individuals should focus on expanding services, enhancing provider education, and promoting cultural sensitivity to meet the growing need for palliative care integration. Funding: This study was supported in part by grants from the National Cheng Kung University Hospital (NCKUH-11305001, NCKUH-V101-10) and the National Health Research Institutes (NHRI-13A1-CG-CO-04-2225-1). The sponsors had no influence on the study.